Changes in different salivary biomarkers related to physiologic stress in elite handball players: the case of females - Mariscal, G.; Vera, P.; Platero, J. L.; Bodi, F.; de la Rubia Orti, J. E.; Barrios, C. (Scientific Reports, 2019)
This study evaluates pre- and post-match concentrations of salivary cortisol, alpha-amylase (AA) and immunoglobulin A (lgA) in a group of 21 elite female handball players in the Spanish national women`s league. The players` mean age was 23.0 ± 5.4 years. The concentration of the biomarkers was determined using ELISA. Mean playing time was 25.2 min. The players` cortisol concentration increased significantly (p < 0.05) whereas the IgA concentration fell significantly (p < 0.01) at the end of the match. There were no significant changes in the concentrations of AA between pre and post-match timepoints. The changes observed in the study also depended on the position played; defenders exhibited the highest cortisol and lowest IgA concentrations after the match. Larger changes in cortisol and IgA were seen in those who played for more than 30 min. The present study shows that a competitive handball match increases physiologic stress in females, with activation of the hypothalamic-pituitary-adrenal axis and the adrenergic system, resulting in decreased immunocompetence.